Bituminous coal-based hard carbon negative electrode material based on oxygen treatment, preparation method and application
By treating bituminous coal with oxygen, introducing oxygen-containing functional groups to optimize the carbon layer spacing and surface activity, forming a high defect density hard carbon structure, solving the first Coulomb efficiency and low sodium storage capacity of bituminous coal-based sodium electro-negative electrode materials, and achieving efficient sodium ion battery performance improvement and cost reduction.
Patent Information
- Application Number
- CN202510425005.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-07-04
AI Technical Summary
In the prior art, the first Coulodium-based sodium electro-negative electrode materials have low efficiency and sodium storage capacity, making it difficult to meet the needs of efficient energy storage.
By treating bituminous coal with oxygen, oxygen-containing functional groups such as hydroxyl and carboxyl groups are introduced, the carbon layer spacing and surface chemical activity are optimized, and hard carbon structure with high defect density is formed, thereby improving electron transport performance and sodium ion diffusion rate.
The first coulomb efficiency and sodium storage capacity of sodium ion batteries have been significantly improved, achieving a first coulomb efficiency of up to 91.1% and a specific capacity of 291.5mAh/g, reducing production costs.
Smart Images

Figure CN120261568A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium-ion batteries, and specifically relates to a bituminous coal-based hard carbon anode material based on oxygen treatment, a preparation method and an application thereof. Background Art
[0002] With the increasing global demand for renewable energy, the importance of efficient energy storage systems has become more prominent. Sodium-ion batteries, with their abundant sodium resources and wide availability, have become a powerful alternative for large-scale grid energy storage. Hard carbon has attracted much attention due to its cost-effectiveness, environmental sustainability, and wide sources. Hard carbon can be obtained from various raw materials such as biomass, polymers, asphalt, and coal, among which coal has attracted much attention due to its low cost, abundant reserves, and high carbon yield. Therefore, coal-based carbon materials are expected to play an important role in large-scale energy storage.
[0003] Bituminous coal is a medium-rank coal with low oxygen content and high reactivity. Its high-temperature carbonization undergoes a typical liquid-phase carbonization process and is more likely to form a graphite carbon structure. Therefore, the key to preparing high-performance hard carbon anodes from bituminous coal lies in suppressing the long-range graphitization of internal microcrystals in the coal structure during the thermal conversion process. In addition, it can be inferred that by doping oxygen into hard carbon, excellent sodium storage capacity and electronic conductivity can be obtained. Summary of the Invention
[0004] In view of this, the purpose of the present invention is to improve the disadvantages of low initial Coulomb efficiency and low sodium storage capacity of bituminous coal sodium battery anode materials, and thus publicly provide a bituminous coal-based hard carbon anode material based on oxygen treatment, a preparation method and an application thereof. The sodium battery anode material prepared by this method has a high sodium storage capacity of 291.5 mAh / g and an initial Coulomb efficiency as high as 91.1% at a current density of 15 mA / g when applied to sodium-ion batteries.
[0005] It should be noted that the present invention introduces oxygen-containing functional groups such as hydroxyl groups and carboxyl groups into bituminous coal in a directional manner through high-temperature oxidation treatment, synchronously regulates the carbon layer spacing and surface chemical activity, optimizes the electron transport path, and reduces the sodium ion diffusion barrier, thereby significantly improving the sodium storage capacity and initial Coulomb efficiency of the material. Specifically, it includes the following key steps: After crushing bituminous coal, it is mixed with an oxidant, and pre-carbonized in an inert atmosphere by heating to 300-500 °C at a rate of 2-4 °C / min. Through the controllable reaction of the oxidant (such as O2 / O3 mixed gas) with the aromatic ring structure in bituminous coal, the expansion of the carbon skeleton and the in-situ bonding of oxygen-containing functional groups are realized; then deep carbonization treatment is carried out to form a hard carbon structure with a high defect density.
[0006] Compared with the existing technologies (such as the sodium peroxide activation + pitch coating process of anthracite-based soft carbon in CN117623307A), the present invention abandons the acid leaching etching and secondary coating steps, and directly regulates the intrinsic properties of the carbon matrix through oxygen treatment, which not only avoids the environmental risks brought by strong acid corrosion, but also improves the interfacial reaction kinetics through the strong adsorption of oxygen-containing groups and sodium ions. Experiments show that the first discharge specific capacity of the obtained hard carbon anode reaches 290 mAh / g, and the first Coulombic efficiency > 90%, which has more stability advantages than traditional soft carbon materials. The present invention provides an innovative path for the high-value utilization of low-cost bituminous coal.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] The first technical object of the present invention is to provide a preparation method of a bituminous coal-based hard carbon anode material based on oxygen treatment. The bituminous coal-based hard carbon anode material is obtained by first purifying bituminous coal powder, then performing oxygen treatment, and finally performing carbonization treatment on the oxygen-treated bituminous coal powder.
[0009] Specifically, the steps are as follows:
[0010] Step 1: Select commercial bituminous coal as the coal-based hard carbon material, refine and crush it to 3 - 15 μm and sieve to obtain bituminous coal powder for standby;
[0011] Step 2: Mix the bituminous coal powder obtained in Step 1 with a mixed acid and stir for 12 - 24 h;
[0012] Step 3: Add an oxidant to the bituminous coal powder treated in Step 2 and mix. Then, heat it to 300 - 500 °C at a rate of 2 - 4 °C / min in an inert atmosphere for 2 - 5 h of low-temperature pre-carbonization treatment;
[0013] Step 4: High-temperature sinter the bituminous coal powder pre-carbonized in Step 3 to obtain the bituminous coal-based hard carbon anode material.
[0014] Optionally, the mixed acid is a mixture formed by hydrochloric acid, nitric acid and hydrofluoric acid in a mass ratio of 10:20:70, and the mass concentration of the acid solution is 5% - 30%.
[0015] Optionally, the oxidant is one or a combination of hydrogen peroxide, peracetic acid, potassium permanganate, and the mass ratio of the bituminous coal powder to the oxidant during mixing is 1:(0.1 - 2).
[0016] Optionally, the high-temperature sintering is carried out as follows:
[0017] The heating temperature is 900 °C - 1800 °C, the constant temperature time is 1 - 24 h, and the heating rate is 2 - 4 °C / min.
[0018] The second technical object of the present invention is to provide a bituminous coal-based hard carbon anode material based on oxygen treatment prepared by the method as described above.
[0019] The third technical object of the present invention is to provide an application of a bituminous coal-based hard carbon anode material based on oxygen treatment prepared by the method as described above in a sodium-ion battery.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] 1. Improvement in electrochemical performance
[0022] The initial Coulombic efficiency is improved. The anode material of the sodium-ion battery obtained in the present invention has a high sodium storage capacity of 291.5 mAh / g and an initial Coulombic efficiency as high as 91.1% at a current density of 15 mA / g.
[0023] 2. Cost advantage
[0024] The present invention uses coal as a raw material. Coal is the most important primary energy source in China. The coal reserves in China account for about 94% of fossil energy, with the characteristics of wide geographical distribution, low cost, low impurity content, and the presence of primary graphite crystals. Moreover, the raw material production is mature and the acquisition cost is low. Compared with other biomass-based or high-cost precursor materials, the production cost of the anode material is greatly reduced. Description of the drawings
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only the embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained according to the provided drawings without creative efforts.
[0026] Figure 1 SEM photos of Examples 1-3 and the comparative example of the present invention;
[0027] Figure 2 Comparison chart of the first charge-discharge curves of Examples 1-3 and the comparative example of the present invention;
[0028] Figure 3 Pore size distribution curves of Examples 1-3 and the comparative example of the present invention. Detailed implementation manners
[0029] The following will clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts fall within the protection scope of the present invention.
[0030] The term "embodiment" used herein specifically. Any embodiment described as "exemplary" does not have to be construed as superior or better than other embodiments. For the performance index tests in the embodiments of this application, unless otherwise specified, conventional test methods in the art are adopted. It should be understood that the terms described in this application are only for describing specific embodiments and are not used to limit the content disclosed in this application.
[0031] Unless otherwise specified, the technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which this application belongs; other test methods and technical means not specifically noted in this application refer to the experimental methods and technical means commonly adopted by those of ordinary skill in the art.
[0032] To better illustrate the content of this application, numerous specific details are given in the following specific embodiments. Those skilled in the art should understand that this application can still be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well-known to those skilled in the art are not described in detail in order to highlight the gist of this application.
[0033] On the premise of no conflict, the technical features disclosed in the embodiments of this application can be combined arbitrarily, and the obtained technical solutions belong to the content disclosed in the embodiments of this application.
[0034] The present invention discloses a bituminous coal-based hard carbon negative electrode material based on oxygen treatment, a preparation method thereof, and its application in a sodium ion battery.
[0035] To better understand the present invention, the following embodiments are used to further specifically elaborate on the present invention, but it should not be construed as a limitation to the present invention. For some non-essential improvements and adjustments made by those skilled in the art based on the above-mentioned inventive content, they are also considered to fall within the protection scope of the present invention.
[0036] Embodiment 1:
[0037] Step 1: Select Ordos clean coal as the coal-based hard carbon material, refine and crush it to 7 ± 1.5 μm and perform screening.
[0038] Step 2: Mix and stir the bituminous coal powder obtained in Step 1 with the mixed acid for 12 h.
[0039] Step 3: Add the bituminous coal powder treated in Step 2 to hydrogen peroxide and mix. The mass ratio during mixing is 2:1, and it is pre-carbonized in a muffle furnace at 400 °C for 5 h.
[0040] Step 4: Place the bituminous coal powder pre-carbonized in Step 3 in a tubular furnace for heating. The heating temperature is 1400 °C; the constant temperature time is 4 h, and finally the bituminous coal-based sodium battery negative electrode material of Embodiment 1 is obtained.
[0041] Example 2:
[0042] Step 1: Select Ordos clean coal as the coal-based hard carbon material, refine and crush it to 7 ± 1.5 μm and perform screening.
[0043] Step 2: Mix and stir the bituminous coal powder obtained in Step 1 with the mixed acid for 12 h.
[0044] Step 3: Add the bituminous coal powder treated in Step 2 to hydrogen peroxide and mix. The mass ratio during mixing is 10:1, and it is pre-carbonized in a muffle furnace at 400 °C for 5 h.
[0045] Step 4: Place the bituminous coal powder pre-carbonized in Step 3 in a tubular furnace for heating. The heating temperature is 1400 °C; the constant temperature time is 4 h, and finally, the sodium-ion battery anode material based on bituminous coal of Example 2 is obtained.
[0046] Example 3:
[0047] Step 1: Select Ordos clean coal as the coal-based hard carbon material, refine and crush it to 7 ± 1.5 μm and perform screening.
[0048] Step 2: Mix and stir the bituminous coal powder obtained in Step 1 with the mixed acid for 12 h.
[0049] Step 3: Add the bituminous coal powder treated in Step 2 to hydrogen peroxide and mix. The mass ratio during mixing is 1:1, and it is pre-carbonized in a muffle furnace at 400 °C for 5 h.
[0050] Step 4: Place the bituminous coal powder pre-carbonized in Step 3 in a tubular furnace for heating. The heating temperature is 1400 °C; the constant temperature time is 4 h, and finally, the sodium-ion battery anode material based on bituminous coal of Example 3 is obtained.
[0051] To further prove the beneficial effects of the present invention and better understand the present invention, the following comparative examples are used to further clarify the technical features disclosed in the present invention, but it should not be construed as a limitation to the present invention. For other improvements made by those skilled in the art based on the above-mentioned invention content without creative work, they are also considered to fall within the protection scope of the present invention.
[0052] Comparative Example:
[0053] Step 1: Select commercial bituminous coal as the coal-based hard carbon material, refine and crush it to 7 ± 1.5 μm and perform screening.
[0054] Step 2: Mix and stir the bituminous coal powder obtained in Step 1 with the mixed acid for 12 h.
[0055] Step 3: Place the bituminous coal powder processed in Step 2 in a tube furnace for heating at a temperature of 1400 °C; keep the temperature constant for 4 h to obtain a comparative example of the bituminous coal-based sodium-ion battery anode material.
[0056] Perform performance tests on the above-mentioned embodiments. Fabricate the obtained bituminous coal-based sodium-ion battery anode material into a sodium-ion battery. The sodium-ion battery uses the above-mentioned Embodiments 1 to 3 and the comparative example as the anode material, a sodium sheet as the counter electrode, and is assembled with a 1M NaPF6 electrolyte and a separator. Next, perform performance tests on the fabricated sodium-ion battery.
[0057] Figure 1 Scanning electron microscope images of the bituminous coal-based sodium-ion battery anode materials obtained in Embodiments 1 to 3 and the comparative example.
[0058] Perform a constant current charge-discharge test on the sodium-ion battery prepared in Embodiment 1. The test voltage range is 0 to 2.5 V, and the current density is 15 mA / g. The obtained charge specific capacity and initial Coulomb efficiency are as Figure 2 shown.
[0059] As Figure 2 can be seen, the sodium-ion battery prepared in Embodiment 1 has a charge specific capacity of 291.5 mAh / g and an initial Coulomb efficiency of 91.1%.
[0060] Under these conditions, perform a constant current charge-discharge test on the remaining embodiments and the comparative example. The results are as Figure 2 and Table 1 below:
[0061] Table 1
[0062]
[0063]
[0064] In summary, the bituminous coal-based sodium-ion battery anode material prepared by the method of the present invention has a certain improvement in the initial charge-discharge specific capacity. At the same time, the oxygen-treated bituminous coal-based hard carbon sodium-ion battery anode material and its preparation method involved in the present invention are highly innovative and practical, and have broad application prospects in the field of sodium-ion batteries.
[0065] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be obvious to those skilled in the art. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A preparation method of a bituminous coal-based hard carbon anode material based on oxygen treatment, characterized in that, The bituminous coal-based hard carbon anode material is obtained by first purifying bituminous coal powder, then performing oxygen treatment, and finally carbonizing the oxygen-treated bituminous coal powder; The specific steps are as follows: Step 1: Select commercial bituminous coal as the coal-based hard carbon material, refine and crush it to 3-15 μm and screen it to obtain bituminous coal powder for standby; Step 2: Mix and stir the bituminous coal powder obtained in Step 1 with the mixed acid for 12-24 h; Step 3: Add an oxidant to the bituminous coal powder treated in Step 2 and mix. Then, heat it to 300-500 °C at a rate of 2-4 °C / min in an inert atmosphere for 2-5 h of low-temperature pre-carbonization treatment; Step 4: High-temperature sinter the bituminous coal powder pre-carbonized in Step 3 to obtain the bituminous coal-based hard carbon anode material; The high-temperature sintering operation is as follows: The heating temperature is 900 °C to 1800 °C, the constant temperature time is 1-24 h, and the heating rate is 2-4 °C / min.
2. The preparation method of the oxygen-treated bituminous coal-based hard carbon anode material according to claim 1, wherein The mixed acid is a mixture formed by hydrochloric acid, nitric acid and hydrofluoric acid in a mass ratio of 10:20:70, and the mass concentration of the acid solution is 5%-30%.
3. The preparation method of the oxygen-treated bituminous coal-based hard carbon anode material according to claim 1, wherein The oxidant is one or a combination of hydrogen peroxide, peracetic acid, potassium permanganate, and the mass ratio of the bituminous coal powder to the oxidant is 1:(0.1-2).
4. An oxygen-treated bituminous coal-based hard carbon anode material prepared by the method according to any one of claims 1-3.
5. Application of an oxygen-treated bituminous coal-based hard carbon anode material prepared by the method according to any one of claims 1-3 in a sodium-ion battery.
Citation Information
Patent Citations
Novel preparation method of anthracite sodium electric soft carbon negative electrode material
CN117623307A
Cited By
Preparation method of coal-based hard carbon material as well as material and application thereof
CN121800174A